Análise e subjetividade : a gênese do "eu" no primeiro Wittgenstein - Michetti, Gustavo Gueraldini (2017)
This dissertation aims to understand the importance of the subject to the philosophy of the first Wittgenstein. Part of the thesis that João Vergílio Cuter develops in his article "Por que o Tractatus necessita de um sujeito transcendental?" Cuter clarifies that, in the Tractatus, the subject is characterized as a logical necessity, responsible for naming and operating on the meaning of a proposition. The purpose of this dissertation is to examine, in the texts that precede the work of 1921, the genesis of this subject absolutely necessary for the constitution of the propositional meaning. To that end, I examine how the concept of analysis is closely linked to the concept of proposition in the years 1913 and 1914, in Notes on Logic and Notes dictated to Moore. I analyse how, in the Notebooks (1914-1916), this concept constitutes a problem for the autonomy of logic and for the task of philosophy. Later, in the 1915 and 1916 notes, it is noted that the "I" is closely linked to the resolution of this problem. With this examination, it is possible to recognize that the notion of subject is fundamental for the resolution of the questions present in the philosophical path of the first Wittgenstein and, therefore, it is possible to establish the genesis of this notion for the Tractatus.